Uji Antimikroba Sabun Cuci Tangan dengan Senyawa Aktif Ekstrak Kayu Manis (Cinnamomum burmannii) terhadap Staphylococcus epidermidis dan Microsporum canis - Riski Dwimalida; Dori Fitria; Deliza; Syukriya Ningsih; Badariah; Wiji Utami; Galih Eka Aurellia (CV. Multi Kreasi Media, 2022)
Hands are parts of the body that are susceptible to being a medium for the transfer of microorganisms. One of the efforts made to prevent transmission is to maintain hand hygiene by washing hands and using soap. Not only is Covid 19 a concern at this time, but several diseases are easily transferred through hand transmission, including tinea capitis or ringworm that attacks the scalp and several abscesses on the skin such as acne. The use of good hand soap will help kill bacteria, fungi, and viruses. In this study, hand washing soap was made with the addition of cinnamon extract (Cinnamomum burmannii) as the active compound. Antimicrobial tests were carried out on Staphylococcus epidermidis and Microsporum canis bacteria. Anti-microbial test results showed that hand soap with cinnamon extract could inhibit the growth of Staphylococcus epidermidis bacteria which was indicated by a 15 mm clear zone and inhibited Microsporum canis fungus with a 14.9 mm clear zone. Organoleptic tests were also carried out on 30 panelists. Parameters tested were aroma, texture, shape, and color. A statistical test showed hand soap with the addition of cinnamon extract was preferred, especially on the odor and color parameters. Keywords: antimicrobial, cinnamon, methanol extract